Inside The Quartet - A first-person virtual reality string quartet production - Meyer-Kahlen, Nils; Piiroinen, Petra; Vishwanath, Gautam; Juntunen, Petri; Tiainen, Eero; Schlecht, Sebastian J. (AES Europe 2023: 154th Audio Engineering Society Convention, 2023)
“Inside the Quartet” is a virtual reality experience that provides users with a first-person perspective of playing in a string quartet. The user can see and hear the music performance from the different players’ perspectives, experiencing how musicians communicate with gestures and eye contact from within the quartet. The VR experience shows recordings of the Kamus string quartet playing Sibelius’s string quartet in D-Minor op. 56 “Voces Intimae” in Ainola, Jean Sibelius’s home in Järvenpää, Finland. The audio production employed spot mics encoded to 5th-order Ambisonics, which were dynamically decoded to headphones during playback. The installation was shown at various music and VR festivals. Here, we describe the audio and video production, rendering workflow, and the challenges and future perspectives for similar VR experiences.
CRIS-Team Scopus Importer:2023-11-06